Some thoughts on the mitochondrial transfer: a new issue for bioethics? - De Miguel Beriain, Iñigo; Atienza Macías, Elena; Armaza Armaza, Emilio José (Acta Bioethica, 2016)
In February 2015 the United Kingdom took the first step towards the adoption of mitochondrial transfer as a therapeutic technique. Theoretically, it will make it possible for many women to get rid of pathologies associated with mitochondrial defects. However, this practice has been subjected to severe doubts from an ethical standpoint. Among these objections, we could highlight the following: its close association with human cloning; the alteration of the germline genes; the modification in the identity of the human being involved; the destruction of human embryos; or the high risk to the health of the human being. In this text we will analyze these objections critically, highlighting the strength of all of them. As a result, we will call for a careful restriction of the use of this technique, and the promotion of the use of alternative options much more respectful of the human future.